The Effect of Leadership Style, Organizational Culture and Work Environment on Employee Performance at CV Shuto Jaya Bersama - Djatmika, Gatot Hery; Ningsih, Putu Tirta Sari; Harsono, Budi; Alviah, Nuvikha (Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
This study aims to determine the effect of Leadership Style, Organizational Culture and Work Environment on Employee Performance at CV Shuto Jaya Bersama. The method used in this study uses a descriptive quantitative method. This study was conducted by looking for primary data with a sample of 50 respondents of CV Shuto Jaya Bersama employees. The data processed with statistical analysis with validity tests, reliability, classical assumption tests, multiple linear regression analysis, hypothesis testing through t-tests and F-tests, and determinant coefficient analysis (R). From the results of the analysis, it shows that the results of the multiple linear regression test are Y = 0.972 + 0.291 Xı + 0.531 X₂ + 0.298 X₃. The results of the t-test indicate that the leadership style of organizational culture and work environment each have a partial positive and significant effect on Employee Performance at CV Shuto Jaya Bersama. The results of the F test show that H0 is rejected and Ha is accepted with an Fcount value of 29.874> Ftable 2.80 at a significant 0.000 <Ftable 0.05. So the F test shows that Leadership Style, Organizational Culture and Work Environment have a simultaneous positive and significant effect on Employee Performance at CV Shuto Jaya Bersama with a percentage of determination coefficient results of 66%. The study shows that the performance of CV Shuto Jaya Bersama employees is good. With this good performance, it can have a positive impact on the progress of the organization and provide satisfaction to customers.